Ascophyllum nodosum Based Extracts Counteract Salinity Stress in Tomato by Remodeling Leaf Nitrogen Metabolism - Emilia Dell’Aversana; Valerio Cirillo; Michael James Van Oosten; Emilio Di Stasio; Katya Saiano; Pasqualina Woodrow; Loredana Filomena Ciarmiello; Albino Maggio; Petronia Carillo (Plants, 2021)
Biostimulants have rapidly and widely been adopted as growth enhancers and stress protectants in agriculture, however, due to the complex nature of these products, their mechanism of action is not clearly understood. By using two algal based commercial biostimulants in combination with the Solanum lycopersicum cv. MicroTom model system, we assessed how the modulation of nitrogen metabolites and potassium levels could contribute to mediate physiological mechanisms that are known to occur in response to salt/and or osmotic stress. Here we provide evidence that the reshaping of amino acid metabolism can work as a functional effector, coordinating ion homeostasis, osmotic adjustment and scavenging of reactive oxygen species under increased osmotic stress in MicroTom plant cells. The Superfifty biostimulant is responsible for a minor amino acid rich-phenotype and could represent an interesting instrument to untangle nitrogen metabolism dynamics in response to salinity and/or osmotic stress.